One year experience with fast track algorithm in patients with refractory out-of-hospital cardiac arrest. (November 2019) - Adler, Christoph; Paul, Christian; Michels, Guido; Pfister, Roman; Sabashnikov, Anton; Hinkelbein, Jochen; Braumann, Simon; Djordjevic, llija; Blomeyer, Ralf; Krings, Andrea; Böttiger, Bernd W.; Baldus, Stephan; et al.
Abstract: Background: Overall prognosis in patients with out-of-hospital cardiac arrest (OHCA) remains poor, especially when return of spontaneous circulation (ROSC) cannot be achieved at the scene. It is unclear if rapid transport to the hospital with ongoing cardiopulmonary resuscitation (CPR) improves outcome in patients with refractory OHCA (rOHCA). The aim of this study was to evaluate the effect of a novel fast track algorithm (FTA) in patients with rOHCA. Methods: This prospective single-center study analysed outcome in rOHCA patients treated with FTA. Historical patients before FTA-implementation served as controls. rOHCA was defined as: persistent shockable rhythm after three shocks and 300 mg of amiodarone or persistent non-shockable rhythm and continuous CPR for 10 min without ROSC after exclusion of treatable arrest causes. Results: 110 consecutive patients with rOHCA (mean age 56 ± 14 years) were included. 40 patients (36%) were treated with FTA, 70 patients (64%) served as historical controls. Pre-hospital time was significantly shorter after FTA implementation (69 ± 18 vs. 79 ± 24 min, p = 0.02). Favourable neurological outcome (defined as cerebral performance categories Score 1 or 2) was significantly more frequent in FTA patients (27.5% vs. 11.4%, p = 0.038). FTA-implementation showed a trend towards improved mortality (70.0% vs. 82.9%, p = 0.151). Extracorporeal Life Support was similar between the two groups. Conclusion: Our study suggests that a rapid transport algorithm with ongoing CPR is feasible, improves neurological outcome and may improve survival in carefully selected patients with rOHCA.